A novel risk signature based on autophagy-related genes to evaluate tumor immune microenvironment and predict prognosis in hepatocellular carcinoma. (January 2023) - Li, Quanxiao; Wu, Jiaqiao; Zhu, Meiyan; Tang, Yuhao; Jin, Limin; Chen, Yong; Jin, Meng; Peng, Zhenwei
Abstract: Hepatocellular carcinoma (HCC) is considered a lethal disease due to the poor prognosis and the limited therapeutic efficacy. Much more attention is being attached to the role of autophagy in HCC, and the relationship between autophagy and tumor immune microenvironment. Therefore, we developed a novel prognostic risk signature based on autophagy-related genes (ARGs) for HCC patients using gene expression profiles collected from TCGA dataset. This 2-ARG-based signature (BIRC5 and SNRPB) was validated in ICGC and GSE14520 datasets, achieving a favorable performance in both overall survival and recurrence-free survival outcomes. Additionally, the autophagy gene signature could independently predict overall survival of HCC after adjusting clinicopathological indicators in three independent datasets. A nomogram including autophagy gene signature and TNM stage was built to serve clinical practice. Significantly, differential abundance of immune cells was shown in different risk groups and the critical immune checkpoints and immunosuppressive cytokines were upregulated in the autophagy high-risk group. Furthermore, the expression levels of proteins encoded by BIRC5 and SNRPB were validated in cell lines by western blot and in tissue samples by immunohistochemistry. In summary, the 2-ARG-based prognostic risk signature could be a useful tool to identify risk subgroups, evaluate immune microenvironment and provide therapeutic targets for HCC patients. Highlights: A prognostic risk signature based on 2 ARGs (BIRC5 and SNRPB) was developed to identify risk subgroups. The signature could be a useful tool to evaluate immune microenvironment and predict OS and RFS in HCC. The signature could serve as an independent prognostic factor for patients with HCC. The expression of BIRC5 and SNRPB was validated in different cell lines and tissue samples.